Metode Bermain Peran PENGARUH METODE BERMAIN PERAN DALAM MATERI WAWANCARA BAHASA SUNDA SISWA FASE E SMA NEGERI 1 LEMBANG - Poppy Sofia; Dingding Haerudin (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
The research is aim at elaborating the impact of role-play method in interview material for phase E (grade X) at SMAN 1 Lembang in Sundanese (Bahasa Sunda) Local Content Subject. The research used experimental quantitative research design. Experimental data for this research were students of SMAN 1 Lembang in odd semester of the 2022/2023 academic-year. In this research, phase E6 students were chosen as experimental class while phase E2 students were chosen as control class. The procedure of collecting data was carried out by observation method through observation sheets and performance test. The result of this research indicated that tcount > ttable (11.309 > 1.99495), consequently H0 was rejected. This showed that role-playing method in interview material had an impact toward phase E students at SMAN 1 Lembang. Keywords: role-play, interview